1979
DOI: 10.1111/j.1423-0410.1979.tb02273.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Inhibition of Specific Agglutination by Plasma Due to Microvesicles Released from Human Red Cells during Storage for Transfusion

Abstract: The progressive appearance of erythrocyte antigenic activity in plasma from donations of human blood taken into acid citrate-dextrose (ACD) and stored at 4 degrees D for transfusion has been studied. It has been shown by specific inhibition tests that A, B, H and P1 activities are associated with membrane-bounded microvesicles which are released from the red cell membrane during the disc-echinocyte-spherocyte shape transformation. Although M group activity appears to be lost from the red cell membrane during s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…They demonstrated that when the intracellular Ca 2+ concentration was increased by treatment with A23187, a bivalent cation ionophore, there was a shape change from discocytes to echinocytes, the 1,2‐diacylglycerol content of the membranes increased, and microvesicles budded from the microvillous‐like projections of the echinocytes. These vesicles were depleted in phosphatidylcholine, spectrin, actin (band 5), and glycophorin, and band 3 and acetylcholinesterase (AChE) were retained 34,58‐61 …”
Section: Rbc Vesiculationmentioning
confidence: 99%
“…They demonstrated that when the intracellular Ca 2+ concentration was increased by treatment with A23187, a bivalent cation ionophore, there was a shape change from discocytes to echinocytes, the 1,2‐diacylglycerol content of the membranes increased, and microvesicles budded from the microvillous‐like projections of the echinocytes. These vesicles were depleted in phosphatidylcholine, spectrin, actin (band 5), and glycophorin, and band 3 and acetylcholinesterase (AChE) were retained 34,58‐61 …”
Section: Rbc Vesiculationmentioning
confidence: 99%